Dr. Nina Škrk Dolar, Jesenkova nagrajenka za najboljšo diplomantko doktorskega študija v letu 2026 - Čufar, Katarina (Les (Ljubljana), 2026)
The Jesenko Awards of the Biotechnical Faculty, University of Ljubljana (BF UL), are the highest awards for pedagogical, research and professional achievements, and for economic and general social progress in the biotechnical field in Slovenia. Among them is also the Jesenko Award for the best doctoral graduate. In 2026 it was awarded to Dr Nina Škrk Dolar, who completed her doctoral study within a young researcher program at the Department of Wood Science and Technology BF UL.
Keywords: Biotechnical Faculty; Biotechnical Faculty award; Biotehniška fakulteta; Jesenko Award; Jesenkova nagrad; Škrk Dolar, Nina